Pola pencarian pengobatan dan peran pengobatan tradisional sebagai bantuan pertama pada pasien laki-laki dengan skizofrenia - Liza Fathiariani; Maidar Maidar; Hermansyah Hermansyah; Fahmi Ichwansyah; Asnawi Abdullah (Holistik Jurnal Kesehatan, 2026)
Background: Introduction: Treatment-seeking patterns for schizophrenia patients in developing countries often involve indirect access to formal health services. Traditional and spiritual healing remain common initial pathways, particularly in strong cultural and religious contexts. Purpose: To describe treatment-seeking patterns and analyze factors associated with the use of traditional medicine as first aid in male patients with schizophrenia. Method: This quantitative, cross-sectional study was conducted from August to December 2025 at the Aceh Provincial Mental Hospital. The sampling technique used was purposive sampling, with a sample size of 155 respondents. The independent variables in this study were age, age of psychosis onset, education level, employment status, marital status, residence, distance to mental health services, internalized stigma as measured using the Internalized Stigma of Mental Illness Scale (ISMI-10), social support as measured using the Multidimensional Social Support Scale (MSPSS), and symptom severity as assessed using the Positive and Negative Syndrome Scale – Joy Component (PANSS-EC). The dependent variable was the use of traditional medicine. Bivariate analysis used the Chi-square test, Fisher's exact test, independent t-test, or Mann–Whitney U test. Results: A total of 57.4% of respondents used traditional medicine as first aid before accessing formal health services. Bivariate analysis showed no significant association between the use of traditional medicine and age (p=0.389), age of onset (p=0.997), education level (p=0.680), marital status (p=0.500), employment status (p=0.784), or domicile (p=0.333). Multivariate analysis also showed no factors significantly associated with the use of traditional medicine. Conclusion: Traditional medicine remains the dominant initial pathway for seeking help among male patients with schizophrenia in Aceh. Demographic factors were not significantly associated with the choice of treatment pathway.   Keywords: First Aid; Male Patients; Schizophrenia; Treatment Seeking Patterns; Traditional Medicine.